Pengaruh E-WOM Dan Kualitas Pelayanan Terhadap Pengguna Jasa Send Delivery Di Kota Langsa - Muhammad Raffi; Erni Junaida; Rahmi Meutia (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The purpose of this study is to explain the effect of E-WOM, and service quality on the use of Send Delivery services in Langsa City. This survey was conducted to users of Send Delivery services in the city of Langsa. This type of research uses quantitative. The sampling technique used purposive sampling with a sample size of 96 respondents. The data collection method used a questionnaire with a Likert scale. The data analysis method used in this study is multiple linear regression analysis using a significant level of 0.05. The results show that E-WOM and service quality have a significant positive effect on users of Send Delivery services with an R Square of 0.438 meaning that E-WOM and service quality affect users of Send Delivery services in Langsa City by 43.8%, while the remaining 0.562 or 56. ,2% of Send Delivery service users in Langsa City are influenced by other factors such as promotion, brand image, price and others.